Traditional Processing of Red Moke Arak from Lontar Palm Sap in Aimere District, Ngada Regency - Bao, Antonia P.; Limbu, Umbu N.; Lea, Victoria Coo (Jurnal Biologi Tropis, 2025)
Aimere is one of the districts in Ngada Regency that has many moke factories using palm sap and has been passed down throught generations as a source of livelihood for the community. This research aims to gather information about the process of red moke arak produced, the factors influencing its production, and marketing strategies. The research uses an exploratory descriptive method with data collection techniques including observation, interviews, and documentation. The results show that the production of red moke arak goes throught palm sap fermentation, distillation, spice addition, soaking of red moke arak and spices, filtration, and storage. Factors influencing production include the quality of palm sap, fermentation process, cleanliness of equipment, temperature, spices, spice soaking time, and storage method. The marketing strategy for red moke arak still uses simple methods thru stalls and social media, with the price per jumbo jerrycan being Rp. 1,000,000, while in 700 ml bottles it is sold for Rp. 35,000 – 40,000. The moke product produced has great potential for economic profit, so it is hoped that the marketing of this product will be expanded with more adequate sales techniques and brand labels, allowing it to be safely marketed to other areas beside Ngada Regency.